2016
DOI: 10.3390/cancers8010013
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation in Neuroblastoma

Abstract: Neuroblastoma, the most common extracranial solid tumor of childhood, continues to carry a dismal prognosis for children diagnosed with advanced stage or relapsed disease. This review focuses upon factors responsible for cell proliferation in neuroblastoma including transcription factors, kinases, and regulators of the cell cycle. Novel therapeutic strategies directed toward these targets in neuroblastoma are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 170 publications
(185 reference statements)
0
32
0
1
Order By: Relevance
“…Several transcription factors have been shown to be involved in the pathogenesis of neuroblastoma by enhancing cancer cell proliferation ( 7 ). MYCN proto-oncogene, bHLH transcription factor ( MYCN ), one of these transcription factors, is a phosphoprotein in the MYC family of transcription factors, encoded by the MYCN oncogene ( 7 ). The amplification of MYCN is one of the first most important genetic signatures of neuroblastoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several transcription factors have been shown to be involved in the pathogenesis of neuroblastoma by enhancing cancer cell proliferation ( 7 ). MYCN proto-oncogene, bHLH transcription factor ( MYCN ), one of these transcription factors, is a phosphoprotein in the MYC family of transcription factors, encoded by the MYCN oncogene ( 7 ). The amplification of MYCN is one of the first most important genetic signatures of neuroblastoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma is an embryonal tumor of the sympathetic nervous system, arising during fetal or early postnatal life from sympathetic cells derived from the neural crest (1). In children, it is the most common extracranial solid tumor, representing approximately 7% of childhood malignancies and up to 15% of childhood cancer mortality (2). The median age of diagnosis is 22 months (3) and it rarely presents in adolescence and adulthood (4).…”
Section: Introductionmentioning
confidence: 99%
“…Management of this malignancy remains a challenge. Recently, we have witnessed a rise in the incidence of neuroblastoma with a very poor prognosis in children diagnosed after the age of 2 years, where the 5-year survival rate is only 38% (2). The heterogeneous nature of this disease makes treatment options tricky because different treatment strategies are indicated on a case by case basis, depending on the nature of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its multiple targets, further evaluations have demonstrated the efficacy of PON in affecting other important tyrosine kinases, including EGFR, FGFR, PDGFR, and VEGFR, which are aberrantly activated in different malignancies [ 6 ]. The mechanisms of action of PON include the regulation of several intracellular signaling pathways, such as STAT3, PI3K/AKT, and ERK, which are all involved in supporting tumor cell proliferation and survival [ 7 ]. However, some studies have found an increased rate of resistance to PON in either pre-clinical or clinical settings [ 8 10 ], and a similar finding may therefore be possible in neuroblastoma, in which the efficacy of PON emerged from both in vitro and in vivo pre-clinical assessments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%